Perilaku Konsumtif Subkultur Pemuda Pada Game Grand Theft Auto Roleplay “Executive Roleplay” - Hidayat, Astra Shada; Agnes Silvia, Jayanti Hemakumari; Wempi, J. A. (Universitas Prof. Dr. Moestopo (Beragama), 2024)
The consumerist behavior among young people, solely aimed at fulfilling desires, is increasingly prevalent, from streaming to playing online games. In the game GTA V Roleplay, there is a donation or sales system involving virtual items designed to enhance the role-playing experience and the sense of reality in the game. Many players spend millions of rupiahs to purchase these virtual items purely for entertainment or to boost their status within the game. This undoubtedly impacts the consumerist influence exerted by these GTA V Roleplay players in pursuit of their satisfaction while playing the game. To comprehend and analyze the phenomenon of teenage consumptive behavior in the game GTA V